ALTERNATE SKIP IRRIGATION STRATEGY ENSURE SUSTAINABLE SUGARCANE YIELD - M. U. Chattha; M. U. Hassan; I. Khan; M. B. Chattha; H. Munir; M. Nawaz; A. Mahmood; M. Usman; M. Kharal (Journal of Animal and Plant Sciences, 2017)
Skip irrigation is one known strategy for crop growth with compromise on cane yield, however, alternate skip irrigation is relatively better and modern strategy for saving water without compromising on cane yield. The experiment was conducted at Sugarcane Research Institute Faisalabad, under randomized complete block design with four replications. Conventional irrigation, combinations of both skip irrigation and alternate skip irrigation techniques were made associated with levels of irrigation at 50%, 75% and 100% of total delta of water for sugarcane at the same location employing 120 cm apart deep trenches. Sugarcane variety HSF-240 fertilized with standard NPK doses @ 168:112:112 kg ha-1 along with mechanical and chemical weed control by using Gezapax Combi @ 3.75 kg ha-1. Furadon granules @ 35 kg ha-1 were applied to control insects. Results revealed that growth parameters were affected and quality traits except cane juice percentage were not affected significantly by different irrigation methods and water levels during the experimental years. Maximum stripped cane yield per hectare was obtained from application of 4000 mm water which was statistically similar to alternate skip irrigation of 3000 mm hence resulted 1000 mm water saving with non-significant compromise on cane and sugar yield.
Keywords: Sugarcane; Irrigation methods; Water Saving